Utilizing business intelligence in revenue forecasting : Case study in a global software company - Laine, Janina (My University, 2020)
This thesis explores the utilization of business intelligence (BI) in revenue forecasting and sheds light especially on a Software as a Service (SaaS) model and on the most used revenue model within SaaS companies, a subscription revenue model. SaaS is a cloud computing model whereby software solutions are delivered to customers over the Internet. The rise of cloud computing has changed the way companies provide software solutions and correspondingly influenced the selection of revenue models. The subscription revenue model provides the software company with a predictable and recurring stream of revenue. BI has been introduced to meet the increasing needs of organizations to analyze and utilize large data sets in order to gain competitive advantage in a highly fast-changing and global business environment. Especially, BI is found to support management accounting in providing valuable business insights for decision-making. When it comes to forecasting with BI, it was found that multiple functionalities support the use of BI in forecasting such as predictive analytics, data integration, data visualization, and information dissemination. This study was conducted as an intensive case study in a global software company focusing on the function of business controlling. The aim of this thesis was to analyze the current state of revenue forecasting in the case company and identify challenges concerning the current state. Furthermore, the objective was to establish a description of the ideal state of revenue forecasting and examine possibilities to utilize BI in revenue forecasting. The empirical evidence for the study was gathered from semi-structured interviews, participant observation, and internal documentation. The empirical findings indicate that there are several challenges in current revenue forecasting in the case company. The challenges concern a manual and time-consuming Excel-based process which requires retrieving of data from different data sources and combining that manually in spreadsheets. Issues were identified also in the level of information the forecast provides and in the frequency of forecasting. Consequently, a number of improvement needs in revenue forecasting were identified with regard to process, systems and tools, information, analysis, and people. The empirical results show that the use of BI in forecasting must be looked at from two perspectives; the preparation of the forecast figures and the analysis of the forecast. In order to use BI for producing the actual figures for the revenue forecast in the case company, some changes to the current ways of collecting and storing data should be done. However, it was found that the use of BI could provide multiple benefits for business controlling such as increased ability to perform comprehensive analysis, automated KPI reporting, and reduced amount of manual work.

Tässä tutkielmassa tarkastellaan business intelligencen (BI) hyödyntämistä liikevaihdon ennustamisessa tutkimalla erityisesti Software as a Service (SaaS) -mallia ja SaaS-yritysten eniten käyttämää tilausmaksuperusteista ansaintamallia. SaaS on pilvipalvelumalli, jonka avulla palveluntarjoaja toimittaa ohjelmistot asiakkailleen Internetin välityksellä. Pilvipalvelujen kasvu on muuttanut tapaa, jolla yritykset tarjoavat ohjelmistoratkaisujaan ja vastaavasti vaikuttanut ansaintamallien valintaan. Tilausmaksuperusteinen ansaintamalli tarjoaa ohjelmistoyritykselle ennustettavan ja toistuvan tulovirran. BI on kehitetty vastaamaan organisaatioiden jatkuvasti kasvaviin tarpeisiin analysoida ja hyödyntää dataa kilpailuedun saavuttamiseksi nopeasti muuttuvassa ja globaalissa liiketoimintaympäristössä. BI:n on todettu erityisesti tukevan johdon laskentatoimea tarjoamalla arvokkaita näkemyksiä liiketoiminnasta päätöksenteon tueksi. Useiden BI:n toiminnallisuuksien havaittiin tukevan BI:n käyttöä ennustamisessa, esimerkiksi: ennustava analytiikka, datan integrointi, datan visualisointi ja informaation jakaminen. Tämä tutkimus suoritettiin intensiivisenä tapaustutkimuksena kansainvälisessä ohjelmistoyrityksessä keskittyen business controlling -funktioon. Tämän tutkielman tavoitteena oli analysoida kohdeyrityksen liikevaihdon ennustamisen nykytila ja tunnistaa siihen liittyviä haasteita. Tutkielman tavoitteena oli lisäksi kuvailla liikevaihdon ennustamisen tavoitetila ja tutkia, kuinka BI:tä voitaisiin hyödyntää kohdeyrityksen liikevaihdon ennustamisessa. Tutkimuksen empiirinen aineisto koostuu puolistrukturoiduista haastatteluista, osallistuvasta havainnoinnista ja yhtiön sisäisestä dokumentaatiosta. Empiiriset havainnot osoittavat, että kohdeyrityksen nykyisessä liikevaihdon ennustamisessa on useita haasteita. Haasteet koskevat ensisijaisesti manuaalista ja aikaa vievää Excel-pohjaista prosessia, joka edellyttää datan keräämistä eri järjestelmistä ja sen yhdistämistä manuaalisesti Excelissä. Haasteita tunnistettiin myös ennusteen tuottaman tiedon monipuolisuudessa sekä ennustamisen ajantasaisuudessa. Vastaavasti, kohdeyrityksessä tunnistettiin liikevaihdon ennustamiseen liittyviä kehitystarpeita prosessin, järjestelmien ja työkalujen, informaation, analyysien ja ihmisten suhteen. Tulokset osoittavat, että BI:n käyttöä ennustamisessa on tarkasteltava kahdesta näkökulmasta: ennustelukujen laatiminen ja niiden analysointi. Jotta BI:tä voitaisiin hyödyntää lukujen laatimiseen, joitain muutoksia datan keruu- ja tallennusmenetelmiin kohdeyrityksessä olisi tehtävä. Tulokset kuitenkin osoittavat, että BI:n käyttö voisi tarjota useita hyötyjä business controllingille, esimerkiksi, parantuneen kyvyn suorittaa kattavia analyysejä, automatisoidun KPI-raportoinnin sekä vähentyneen manuaalisen työn.
Keywords: revenue forecasting, SaaS, business intelligence, global company